ROBUST: A Phase III Study of Lenalidomide Plus R-CHOP Versus Placebo Plus R-CHOP in Previously Untreated Patients With ABC-Type Diffuse Large B-Cell Lymphoma - Nowakowski, Grzegorz S; Chiappella, Annalisa; Gascoyne, Randy D; Scott, David W; Zhang, Qingyuan; Jurczak, Wojciech; Özcan, Muhit; Hong, Xiaonan; Zhu, Jun; Jin, Jie; Belada, David; Bergua, Juan Miguel; et al. (Journal of clinical oncology, 2021)
PURPOSE: Patients with the activated B-cell-like (ABC) subtype of diffuse large B-cell lymphoma (DLBCL) historically showed inferior survival with standard rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). Phase II studies demonstrated that adding the immunomodulatory agent lenalidomide to R-CHOP improved outcomes in ABC-type DLBCL. The goal of the global, phase III ROBUST study was to compare lenalidomide plus R-CHOP (R2-CHOP) with placebo/R-CHOP in previously untreated, ABC-type DLBCL. METHODS: Histology and cell-of-origin type were prospectively analyzed by central pathology prior to random assignment and study treatment. Patients with ABC-DLBCL received lenalidomide oral 15 mg/d, days 1-14/21 plus standard R-CHOP21 versus placebo/R-CHOP21 for six cycles. The primary end point was progression-free survival (PFS) per independent central radiology review. RESULTS: A total of 570 patients with ABC-DLBCL (n = 285 per arm) were stratified by International Prognostic Index score, age, and bulky disease, and randomly assigned to R2-CHOP or placebo/R-CHOP. Baseline demographics were similar between arms. Most patients completed six cycles of treatment: 74% R2-CHOP and 84% placebo/R-CHOP. The most common grade 3/4 adverse events for R2-CHOP versus placebo/R-CHOP were neutropenia (60% v 48%), anemia (22% v 14%), thrombocytopenia (17% v 11%), and leukopenia (14% v 15%). The primary end point of PFS was not met, with a hazard ratio of 0.85 (95% CI, 0.63 to 1.14) and P = .29; median PFS has not been reached for either arm. PFS trends favoring R2-CHOP over placebo/R-CHOP were seen in patients with higher-risk disease. CONCLUSION: ROBUST is the first DLBCL phase III study to integrate biomarker-driven identification of eligible ABC patients. Although the ROBUST trial did not meet the primary end point of PFS in all patients, the safety profile of R2-CHOP was consistent with individual treatments with no new safety signals.
Keywords: senioři; difúzní velkobuněčný B-lymfom; Doxorubicin; cyklofosfamid; senioři nad 80 let; prednison; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Vincristine; Lymphoma, Large B-Cell, Diffuse; Lenalidomide; Aged, 80 and over; Young Adult; Rituximab; doxorubicin; ženské pohlaví; Cyclophosphamide; Humans; Prednisone; rituximab; lidé středního věku; vinkristin; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; lenalidomid; lidé; Male